MONOCLONAL ANTIBODIES WITH ADCC AND CDC ENHANCEMENT FOR THERAPY - KOLLA BRAMHENDRA CHOUDARY (International Journal of Pharma and Bio Sciences, 2013)
Monoclonal antibodies are highly specific molecular-targeted therapeutic agents and represent fastest growing areas of the biopharmaceutical industry. Therapeutic efficacy of antibodies are mediated by variety of mechanisms including binding to antigen on target cells and recruiting effector functions by Fc region such as Antibody Dependent Cellular Cytotoxicity (ADCC) or Complement Dependent Cytotoxicity (CDC). Antibody engineering, glycovariation, engineering of expression host and selection of antibody isotype are powerful approaches for the generation of antibodies with fully human sequence and improved efficacy of ADCC, CDC. Various monoclonal antibodies (mabs) have been developed and approved as immunotherapeutic agents for various human diseases and improvement in efficacy of antibodies continues to be big challenge. Extensive reports have been made to increase the effector functions, here in this review we discuss some approaches like engineering of amino acid sequence in Fc region and glyco-modifications of an antibody for enhancing the binding to FcγR and C1q. These could be great value for the development of next generation of antibody therapeutics with promise clinical efficacy and safety.